2022
DOI: 10.3389/fnagi.2022.986443
|View full text |Cite
|
Sign up to set email alerts
|

The role of brain derived neurotrophic factor in central nervous system

Abstract: Brain derived neurotrophic factor (BDNF) has multiple biological functions which are mediated by the activation of two receptors, tropomyosin receptor kinase B (TrkB) receptor and the p75 neurotrophin receptor, involving in physiological and pathological processes throughout life. The diverse presence and activity of BDNF indicate its potential role in the pathogenesis, progression and treatment of both neurological and psychiatric disorders. This review is to provide a comprehensive assessment of the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 127 publications
0
32
0
2
Order By: Relevance
“…Furthermore, ABCD1 expression in cALD astrocytes was sufficient to mitigate the basal TLR hyperactivation which is quite intriguing. BDNF and CNTF play essential role in neuronal genesis, differentiation, survival and functional maintenance of sympathetic and parasympathetic neurons (Li et al, 2022; Linnerbauer and Rothhammer, 2020). While AMN-OV astrocytes do not show lowering in glycolysis, BDNF, CNTF, and NGF expressions were increased suggesting that ABCD1 induction can enhance neuroprotection in AMN phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ABCD1 expression in cALD astrocytes was sufficient to mitigate the basal TLR hyperactivation which is quite intriguing. BDNF and CNTF play essential role in neuronal genesis, differentiation, survival and functional maintenance of sympathetic and parasympathetic neurons (Li et al, 2022; Linnerbauer and Rothhammer, 2020). While AMN-OV astrocytes do not show lowering in glycolysis, BDNF, CNTF, and NGF expressions were increased suggesting that ABCD1 induction can enhance neuroprotection in AMN phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, another finding was the differential expression of the lncRNA AC0008937.2 in the context of SAD, which—as an antisense lncRNA to MAP3K1 —has a potentially regulative role ( 75 ) in the MAPK signaling cascade. Another important gene that can regulate and is regulated by MAPK signaling is the brain-derived neurotrophic factor (BDNF) ( 76 , 77 ), which is an important player in neurogenesis ( 78 ). The neurotrophin BDNF, which is known to be affected by neuroinflammation ( 79 ), is essential for dendritic development in peripheral and central nervous system and regulates dendritic growth ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides its involvement in multiple neurological disorders such as Alzheimer’s, Parkinson’s and Huntington’s disease, BDNF also participated in depression. Moreover, depression patients have lower serum BDNF levels ( Lee et al, 2007 ; Li et al, 2022b ). It is also reported that inflammatory cytokines can decrease BDNF signaling ( Cortese et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%